PENGELOLAAN CASH FLOW UMKM DIMASA PANDEMI COVID-19 - Nurainun Bangun (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2021)
Kelapa Dua Village is one of the villages in Kelapa Dua District, Tangerang Regency, Banten. The impact of the Covid-19 pandemic is certainly felt by the people of Kelapa Dua Village, the majority of whom are SMEs. The direct impacts felt by the community include health, economic, and psychological impacts. Economic anxiety is the most serious problem, because many SMEs are experiencing a decline in sales and an unstable business climate.In Kelapa Dua Village, SME business actors are mostly engaged in fields that produce daily consumption products, such as food and processed food and beverages as well as other culinary delights. The results of a survey conducted by the Tangerang Regency Government 86% of SMEs use their own capital and 11% obtain capital from bank loans and cooperatives. In the midst of this pandemic, some SMEs are not producing and some are still producing. Those who stopped operating were 17.9%, which produced 11.4% normally and those who continued to produce even though sales had fallen significantly due to the impact of the COVID-19 pandemic were 70.7%. In order to compensate for all these conditions, SMEs are required to work even harder to increase their economic turnover, and seek breakthroughs in order to survive. The key challenge for MSMEs during the pandemic is overcoming operational cash flow problems, as well as implementing changes in business strategies to offer services and products. The purpose of this community service is to participate in reviving the slumped SME business in the form of counseling on Cash Flow Management for SMEs affected by the Covid-19 pandemic. Participants are prioritized for SME actors who are residents of the Kelapa Dua village, Kelapa Dua sub-district, Tangerang. The activity was carried out online via video in mid-November 2021. The activity was attended by 20 MSME participants